2011
DOI: 10.1017/s1368980011000863
|View full text |Cite
|
Sign up to set email alerts
|

Renal impairment and moderate alcohol consumption in the elderly. Results from the Italian Longitudinal Study on Aging (ILSA)

Abstract: Objective: The influence of moderate alcohol consumption on renal function is not clear in elderly people. The aim of the present study was to investigate the relationship between alcohol consumption and renal function, expressed as serum creatinine levels and glomerular filtration rates (GFR), in an elderly population. Design: Perspective cohort study. Setting: Population-based study on an elderly Italian population. Subjects: A sample of 3404 Italian people (1619 women and 1785 men), aged 65-84 years, from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Sex, age, primary diseases, initial GFR, individual differences, and dietary structure can all influence the results of a study. Although associations between alcohol consumption and CKD risk did not show significant interactions with age, sex, smoking, hypertension, or hypercholesterolemia [80], many studies still found that the effect of alcohol consumption on CKD varies with sex [13,14,76,90], as it appears that sex may be a significant determinant of the effects of alcohol on GFR [50,91].…”
Section: Association Between Alcohol Consumption and Chronic Kidney Dmentioning
confidence: 99%
“…Sex, age, primary diseases, initial GFR, individual differences, and dietary structure can all influence the results of a study. Although associations between alcohol consumption and CKD risk did not show significant interactions with age, sex, smoking, hypertension, or hypercholesterolemia [80], many studies still found that the effect of alcohol consumption on CKD varies with sex [13,14,76,90], as it appears that sex may be a significant determinant of the effects of alcohol on GFR [50,91].…”
Section: Association Between Alcohol Consumption and Chronic Kidney Dmentioning
confidence: 99%
“…Three studies included only male participants (Reynolds et al., ; Sato et al., ; Schaeffner et al., ), 1 study included only female subjects (Knight et al., ), and another 11 studies included both male and female participants. Two studies assessed the association between drinking and chronic kidney damage stratified by sex (Buja et al., ; Yamagata et al., ); thus, we regarded one study as 2 independent studies to extract data. The reference groups were non‐drinkers except in 4 studies (Schaeffner et al., ; Shankar et al., ; Wakasugi et al., ; White et al., ) which selected subjects with lower alcohol drinking as reference group (mean level of alcohol drinking < 10 g/d).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies defined the dose of alcohol intake by drinking frequency (Dunkler et al., ; Foster et al., ; Hu et al., ; Koning et al., ; Menon et al., ; Reynolds et al., ; Schaeffner et al., ; Shankar et al., ; Stengel et al., ), and another 6 studies assessed alcohol drinking by the dose of alcohol. Of all the studies, 2 studies chose ESRD as an outcome (Reynolds et al., ; Stengel et al., ), 8 studies chose declined GFR (Buja et al., ; Foster et al., ; Hu et al., ; Knight et al., ; Menon et al., ; Sato et al., ; Schaeffner et al., ; Shankar et al., ), 1 study chose proteinuria (Wakasugi et al., ), and 4 studies included both declined GFR and proteinuria as outcomes (Dunkler et al., ; Koning et al., ; White et al., ; Yamagata et al., ). The major adjusted confounders included age; body mass index; physical activity; smoking; and some basic diseases, such as hypertension, diabetes, and hypercholesterolemia; and the baseline information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations